Kondisi Oseanografi dan Dinamika Konservasi Sumberdaya Pesisir dan Lautan Wilayah Perairan Riau (Jurnal Pilar Sains, 2005)
Condition of regional oceanography coasial area territorial water of Riau represent vitally matter inecosystem its characteristic. This useful data in order to development of environmental resource andresearch into with aim to improve exploiting of resource biotic and abiotic for the shake of prosperityspecially to society of provinsi Riau, which major region in the form of territorial water and ocean. Ironicbut, though resource territorial water of ocean very abundance in the reality prosperity of society veryfar drop behind in exploiting available resource. This research is done with survey and muster data ofoceanography from some source beside identify the condition of territorial water through chemicalparameter and territorial water physics. Is also done by measurement of speed of current, temperature,and salinitas. Result of research indicate that region territorial water of Riau to consisnt of Coastal areaecosystem and sea of Riau that is mangrove ecosystem, field ecosystem ponder, estuaria ecosystem. Whilefrom potency convert oceanic energy that wave and ebb energy very promising for the development andgeneralization electrics energy of Riau.